Penerapan Diversi Dalam Penyelesaian Perkara Tindak Pidana Lalu Lintas Yang Dilakukan Oleh Anak (Studi Kasus Pengadilan Negeri Boyolali) - Nisa, Khoirun; , Dr. Natangsa Surbakti S.H.,M.Hum (2017)
Children are an integral part of human survival and sustainability of a nation and country. So it needs to get the greatest opportunity to grow and develop optimally, both physically, mentally and socially. It is necessary to enforce safeguard to create the children welfare, by providing guarantees of the fulfillment of their rights without the discrimination. In the case of child againts the law for the crime of traffic, imprisonment is not the best option for educating children becuase it will only lead to stigma as criminals who would afflict children and is the beginning of a failure and the beginning of disaster the future. Diversion nowadays becomes one of the legal means considered to be very accommodating in an accomplishment outside of court on criminal cases of traffic carried by children.